EIN NEUES OPTISCHES MESSGERÄT ZUR MESSUNG DER GERADHEIT LANGER BOHRUNGEN - Turi, Z.; Ábrahám, Gy.; Halmai, A.; Huba, A.; Wenzel, K. (Periodica Polytechnica Mechanical Engineering, 1987)
The measurement of workpieces with long but smalldiametric cavitys (drills) is always a difficult problem. The apparatus shown in this paper has been developped for measurement of the straightness of cavitys with 5-10 mm diameter and 600-1000 mm length. The optical principle of this measuring allows to achieve the uncertainty less then ± 5 11 qm.